Adversity Quotient in neurosurgical training - Thapa, Amit (Nepal Journal of Neuroscience, 2020)
Modern education system around the world is based on training to acquire knowledge and skills. How much a student gains largely depends upon his intelligent quotient (IQ). As IQ is not the only factor to determine success in life, some institutions have tried to assess their potential candidates by emotional quotient (EQ). As we build our career, we try develop our Spiritual Quotient (SQ) by behaving with wisdom and compassion while maintaining inner and outer peace. However, we remain largely unware of our Adversity Quotient (AQ), an index which actually measures how an individual face and deals with unpleasant situations so common in neurosurgical practice and present-day competitive world. Over 1500 researches from over 100 universities and institutions globally have supported its role.1,2 The leaders and the successful people have uniformly been shown to display highest AQ! If IQ measures one’s capability, EQ the will, SQ the purpose then AQ measures one’s response to adversity.